Перший приватний міський банк Російської імперії: документознавчий аспект - Пархоменко, Наталія (Видавництво Львівської політехніки, 2013)
The history of the banking system of the Russian Empire. The causes of the formation of the first public private bank. Made a brief description of the organization, functions, allocation of start-up capital, operation and characteristics of urban private bank for example Anfilativskoho bank. The main forms of documents arising from the activities of the bank.
Keywords: банківська система; приватний міський банк; банківські операції 19 століття; банківські документи; форми документів